About time [videorecording (DVD)] - Curtis, Richard, 1956-; McAdams, Rachel, 1978-; Gleeson, Domhnall, 1983-; Nighy, Bill, 1949-; Hollander, Tom, 1967-; Robbie, Margot, 1990- (2014)
The night after another unsatisfactory New Year party, Tim's father tells his son that the men in his family have always had the ability to travel through time. Tim can't change history, but he can change what happens and has happened in his own life, so he decides to make his world a better place by getting a girlfriend. But as his unusual life progresses, Tim discovers that, in the end, making the most of life may not need time travel at all.